The economics of commodity markets - Chevallier, Julien; Ielpo, Florian (Hoboken : Wiley, 2013)
As commodity markets have continued their expansion an extensive and complex financial industry has developed to service them. This industry includes hundreds of participating firms, including asset managers, brokers, consultants, verification agencies and a myriad of other institutions. Universities and other training institutions have responded to this rapid expansion of commodity markets as well as their substantial future growth potential by launching specialized courses on the subject. The Economics of Commodity Markets attempts to bridge the gap between academics and work.
Preface -- List of figures -- List of tables -- Acronyms -- Commodity markets dynamics -- Individual dynamics : from trends to risks -- Cross-commodities linkages -- Commodities and the business cycle -- The reaction of commodity markets to economic news -- Economic regimes and commodity markets as an asset class -- Commodities and fundamental value -- Cross-commodity linkages -- Cointegration with traditional asset markets -- Cointegration with industrial production and inflation -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Primary commodities; Commercial products; Financial futures; BUSINESS & ECONOMICS -- Investments & Securities -- General; Commercial products; Financial futures; Primary commodities; Electronic books; Electronic books; Electronic books